Le privé est politique… et économique ! Pour une économie politique du travail de gestation pour autrui: - Jouan, Marlène; Clos, Clémence (Nouvelles Questions Féministes, 2021)
Dans le débat public sur la gestation pour autrui (GPA), parler de « travail » pour qualifier ce que font les femmes porteuses est largement perçu comme une façon de cautionner les formes de marchandisation et d’exploitation du corps des femmes à l’œuvre dans les circuits mondialisés de la bioéconomie. Contre cette interprétation qui accompagne la condamnation morale de cette pratique reproductive, en particulier dans sa version « commerciale », l’article développe une défense féministe de la conceptualisation de la GPA comme travail, appuyée sur les études ethnographiques menées auprès des femmes porteuses indiennes et nourrie théoriquement à la fois par le marxisme, par l’éthique du care et par la notion d’intersectionnalité. In fine, l’objectif est de mettre en lumière la fécondité de cette conceptualisation non seulement pour la pleine reconnaissance des femmes porteuses, mais aussi pour le diagnostic critique des divisions du travail qui structurent la société capitaliste.
Number: 2
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amérique du nord; amériques; approches et analyses; asie; care; corps; cours; discipline; europe; france; inde; inégalités; maternité; premier cycle; privilèges; procréation; périodes historiques; régions géographiques; santé; sciences humaines; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques; travail; états-unis

« Gender Equality and Economic Inequality: Impact on Marriage » dans Gender and couple relationships - Coontz, Stephanie (Gender and couple relationships, 2016)
Changes in aggregate marriage rates and in the internal dynamics of individual marriages should be understood as the outcome of two powerful but very different trends in gender and class relations. One trend is the uneven but undeniably dramatic progress toward equality in personal life and cultural values, which has led to widespread repudiation of centuries-old gender hierarchies. The other trend is an equally powerful movement toward growing inequality, insecurity, and unpredictability in economic life, which has resulted in substantial losses for the most historically vulnerable and least-educated sections of the workforce. The ongoing gender revolution interacts with widening economic inequality in complex ways, increasing the benefits of marriage for individuals with higher earning power while increasing the risks of marriage for low-income individuals, especially women.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; care; cours; discipline; discours dominant; droits des femmes*; famille; inégalités; mariage; premier cycle; privilèges; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexualité; soc2262; sociologie; systèmes d'oppressions; thématiques; états-unis

Life with the first baby: women's satisfaction with the division of roles - Cappuccini, G.; Cochrane, R. (Journal of Reproductive and Infant Psychology, 2000)
The ways parents divide their roles after their first child is born is a particularly complex arena. The success of negotiations within this close personal relationship may be central to the future of the new family. Women and their partners were surveyed in late pregnancy and 6 months after the birth. Their attitudes to role division remained largely non-traditional after the birth, even though most of them had incorporated some traditional elements into their behaviour. Emotional support received from their partners was important to women's satisfaction with role division, which had fallen only slightly after the birth. Eight of the women were interviewed in depth to explore why it might be that satisfaction with role division tended to remain high after the birth, despite the division usually not being what they had hoped for. Contributory factors may include changes in emphasis in the division of breadwinning and the maintenance of overall responsibility for traditional role areas despite sharing of tasks.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; angleterre; approches et analyses; cours; discipline; europe; hétérosexualité; inégalités; maternité; premier cycle; privilèges; psychologie; périodes historiques; régions géographiques; sciences humaines; sexualité; soc2264; sociologie; systèmes d'oppressions; thématiques